Subcutaneous emphysema of upper limb. Issue 6 (1st November 2001) - De, M; Stevenson, J
Abstract : A case is reported of subcutaneous emphysema involving upper limb resulting from a trivial laceration to the elbow. Gas in the soft tissues after the injury can be caused by infection with a gas forming organism or by a variety of non-infective causes. It is hypothesised that this minor skin wound has acted like a ball-valve mechanism leading to air being trapped in the soft tissue. Emerg Med J (Emerg Med J 2001;18:522)